Multiplexed GTPase and GEF biosensor imaging enables network connectivity analysis - Marston, Daniel J. (Nat Chem Biol, 2020)
Here we generate FRET biosensors for guanine exchange factors (GEFs) by inserting a fluorescent protein pair in a structural “hinge” common to many GEFs. Fluorescent biosensors can map the activation of signaling molecules in space and time, but it has not been possible to quantify how different activation events affect one another or contribute to a specific cell behavior. By imaging the GEF biosensors in the same cells as red-shifted biosensors of Rho GTPases, we can apply partial correlation analysis to parse out the extent to which each GEF contributes to the activation of a specific GTPase in regulating cell movement. Through analysis of spontaneous cell protrusion events we identify when and where the GEF Asef regulates the GTPases Cdc42 and Rac1 to control cell edge dynamics. This approach exemplifies a powerful means to elucidate the real-time connectivity of signal transduction networks.